2020
DOI: 10.1103/physrevapplied.13.034065
|View full text |Cite
|
Sign up to set email alerts
|

Auxetic Tetrahex Carbon with Ultrahigh Strength and a Direct Band Gap

Abstract: Tetrahex-carbon is a recently predicted two dimensional (2D) carbon allotrope which is composed of tetragonal and hexagonal rings. Unlike flat graphene, this new 2D carbon structure is buckled, possesses a direct band gap ~ 2.6 eV and high carrier mobility ~ 10 4 cm 2 / (V·s) with anisotropic feature. In this work, we employ first-principles density-functional theory calculations to explore mechanical properties of tetrahex-C under uniaxial tensile strain. We find that tetrahex-C demonstrates ultrahigh ideal s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Thus direction-dependent tunability of o-B 2 N 2 enables both widening and narrowing of band gap energy over a wide range (0.97-2.92 eV) only through applying tensile strain. Although direction-dependent band gap tunability has already been reported in several 2D materials with intrinsic structural anisotropy such as tetrahex structures (for instance, tetrahex-carbon, tetrahex-SiC, and tetrahex-BN all exhibit this feature with less than 1.0-, 0.5-, and 0.8-eV tunability over 10% tensile strain, respectively [56][57][58]), the ∼2-eV anisotropic tunability found in o-B 2 N 2 makes it outstanding.…”
Section: Resultsmentioning
confidence: 93%
“…Thus direction-dependent tunability of o-B 2 N 2 enables both widening and narrowing of band gap energy over a wide range (0.97-2.92 eV) only through applying tensile strain. Although direction-dependent band gap tunability has already been reported in several 2D materials with intrinsic structural anisotropy such as tetrahex structures (for instance, tetrahex-carbon, tetrahex-SiC, and tetrahex-BN all exhibit this feature with less than 1.0-, 0.5-, and 0.8-eV tunability over 10% tensile strain, respectively [56][57][58]), the ∼2-eV anisotropic tunability found in o-B 2 N 2 makes it outstanding.…”
Section: Resultsmentioning
confidence: 93%
“…Due to the bonding flexibility of carbon atoms, numerous 2D carbon allotropes have been proposed theoretically. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These carbon allotropes exhibit some amazing properties, such as ultrahigh ideal strength, [9] high electron mobility at room temperature, [8] superconductivity, [22] good catalytic activity, [23] ferromagnetism, [24] and negative Poisson's ratio. [9,25] It is no doubt that the fascinating properties will encourage further investigations of these 2D carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this effect, the stress in this work adopts the force per unit length in the unit of N/m. It is found that TH-SiC2 and SiC are more ductile in the x (zigzag) direction, similar to the case of tetrahex-C [42].…”
Section: Mechanical Properties and Mechanical Stabilitymentioning
confidence: 53%
“…Similarly, for the SiC structure in Fig. 1 Table 1 gives a summary of some structural parameters and basic properties of the TH-SiC2 and SiC, along with penta-SiC2 [28], tetrahex-carbon [22,42], penta-graphene [17], graphene and low-buckled silicene [7,27]. Comparing the buckling thickness and two typical bond lengths in TH-SiC2 with those in penta-SiC2, their values are close.…”
Section: Structure and Thermodynamic Stabilitymentioning
confidence: 97%
See 1 more Smart Citation